ChemInform Abstract: Reaction Dynamics in Astrochemistry: Low‐Temperature Pathways to Polycyclic Aromatic Hydrocarbons in the Interstellar Medium. Issue 41 (October 2015) - Kaiser, Ralf I.; Parker, Dorian S. N.; Mebel, Alexander M.
Abstract Review: 96 refs.